Pelapisan aksesoris logam untuk produk kulit menggunakan resin akrilat - Suraswati, Agustin; Suprapto, Suprapto (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2003)
The aim of the research is to aquire an appropriate plating technique on leather product accessories made from metal without lessening the wonderful appearance of the accessories, to maintain the shade and to keep the rust away from the accessories that avoid or diminish defects on the leather. The plating was carried out by spraying using spraying-gun one, two, and three times, and repeated three times for each treatment to chrome plated metal, gold plated metal and roasted metal. The smaples were then pinned on a piece of chrome tanning leather and vegetable tanned leather, whereas the test carried out was wet and dry rub fastness. Data from completely randomized design are analyzed by factorial pattern according to Gasperz (1991), showed that there was not significant effect on plating neither metal on chrome and vegetable tanned leather having been stored for one, two, or three months, neither on similar things having not been stored yet. However there was significant difference on accessories having been do treated as the stated above and set on a piece of vegetable tanned leather stored for three months. Conclusion could be drawn from the research that the use of acrylate using spray system for plating metal accessories was able to maintain its beautiful appearance, kept the rust away, that was not create defects neither on chrome nor vegetable tanned leather. Â Keywords : plating, leather product, metal accessories, acrylate.Â